The integration of liquid and solid muon absorbers into a focusing magnet of a muon cooling channel - Green, M; Black, E; Cummings, M; Kaplan, D; Ishimoto, S; Cobb, J; Lau, W; Yang, S; Palmer, R (2003)
This report describes how one can integrate the muon absorber with the focusing coils of a SFOFO muon cooling channel [1]. The absorber material must be a low Z material that reduces the muon momentum with minimum scattering. The best materials to use for muon ionization cooling absorbers are hydrogen, helium, lithium hydride, lithium, and beryllium. Hydrogen or helium in an absorber would normally be in the liquid state, Lithium hydride, lithium, and beryllium would normally be in the solid state. This report limits the absorber materials discussed to hydrogen, helium, lithium, and beryllium. In order to achieve the same level of ionization cooling with a solid absorber as a liquid hydrogen absorber, the beta of the muon beam must be reduced more than a factor of two. This affects both the designs of the absorber and the magnet around it. Reducing the beam beta reduces the momentum acceptance of the channel. Integration of a liquid hydrogen absorber and solid absorbers with a superconducting focusing solenoid is discussed. The choice of absorber material affects the design of the superconducting focusing magnet and the superconductor that is used to generate the magnetic field.